Less Pay and More Sensitivity? Institutional Investor Heterogeneity and CEO Pay - Shin, Jae Yong; Seo, Jeongil (Journal of Management, 2011)
In this article, the authors develop and test a theory on the effect of institutional investor heterogeneity on CEO pay. Their theory predicts that institutional investors’ incentives and capabilities to monitor CEO pay are determined by the fiduciary responsibilities, conflicts of interest, and information asymmetry that institutional investors face. Their theory suggests, in contrast to previous literature, that public pension funds and mutual funds exert different effects on CEO pay at their portfolio firms because they do not have the same monitoring incentives and capabilities. Using a longitudinal sample of S&P 1500 firms for the years 1998 to 2002, the authors find that public pension fund ownership is more negatively—indeed, oppositely—associated with both the level of CEO pay and CEO pay-for-performance sensitivity than mutual fund ownership. Their findings suggest that (a) researchers’ use of institutional investor classifications that do not distinguish public pension fund ownership and mutual fund ownership can be misleading and (b) while CEO pay critics have called for pay plans that are in line with the “less pay and more sensitivity” principle, this may be an ineffective goal to pursue.